A Review on the Mechanism and Structure-activity Relationship of Resveratrol Heteroaryl Analogues - Xiang, Yijun; Xu, Yao; Li, Jiaxin; Jiang, Jingyi; Wang, Yanjie; Li, Xiaoshun; Ai, Wenbin; Mi, Pengbing; Yang, Zehua; Zheng, Zitong (Combinatorial Chemistry & High Throughput Screening, 2024)
Resveratrol is one of the most interesting naturally-occurring nonflavonoid phenolic compounds with various biological activities, such as anticancer, neuroprotection, antibacterial, and anti-inflammatory. However, there is no clinical usage of resveratrol due to either its poor activity or poor pharmacokinetic properties. Heteroarenes-modified resveratrol is one pathway to improve its biological activities and bioavailability, and form more modification sites. In this review, we present the progress of heteroaryl analogues of resveratrol with promising biological activities in the latest five years, ranging from the synthesis to the structure-activity relationship and mechanism of actions. Finally, introducing heteroarenes into resveratrol is an effective strategy, which focuses on the selectivity of structure-activity relationship in vivo.
Keywords: NPs